2014
DOI: 10.1136/injuryprev-2014-041268
|View full text |Cite
|
Sign up to set email alerts
|

Trends in fall-related injuries among older adults treated in emergency departments in the USA

Abstract: To examine national trends in fall-related injuries among older adults treated in emergency departments (ED) and project these injuries until the year 2030. The Web-based Injury Statistics Query and Reporting System was used to generate data on fall-related injuries treated in ED. Joinpoint regression analysis was used to examine the average annual change in injury rates over time. Fall-related injury and hospitalisation rates increased on average by 2% (95% CI 1.5% to 2.7%) and by 4% (95% CI 2.9% to 5.0%) per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 16 publications
3
39
1
5
Order By: Relevance
“…As with other studies, [29][30][31][32][33][34][35][36] we found significantly higher rates of fall-related injuries among older women compared to older men across all survey years. Loss of bone mineral density following menopause may predispose women to a higher risk of fracture.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…As with other studies, [29][30][31][32][33][34][35][36] we found significantly higher rates of fall-related injuries among older women compared to older men across all survey years. Loss of bone mineral density following menopause may predispose women to a higher risk of fracture.…”
Section: Discussionsupporting
confidence: 73%
“…47 In addition, recent declines in fall-related injury rates have also been reported in the older senior population (Z 80 years) in Finland 48 and may reflect improvements in the functional ability and living environments of older seniors, although further assessment of trends is warranted. In contrast, studies in the USA 30 and Australia 33 have reported notably sharper increases in rates among older rather than younger age groups.…”
Section: -39mentioning
confidence: 67%
See 2 more Smart Citations
“…They are over-represented in injury statistics, and fall-related injuries are recognized globally as a major threat to health and wellbeing [2,3]. By definition, for most people, aging means a decline in personal, physical, cognitive, and social resources or capacity, for example, a decrease in mobility, muscle strength, and balance [4,5].…”
Section: Introductionmentioning
confidence: 99%